Peter Garnsey: Food and Society in Classical Antiquity - Wilkins, John (Petits Propos Culinaires, 2024)
Peter Garnsey: Food and Society in Classical Antiquity: Cambridge University Press, 1999, 189 pp, 9 illustrations; h/b £35, p/b £12.99.